TM3-10 National survey and experimental evaluation of commonly used external ventricular drain (EVD) securement methods in a porcine model; recommendations to improve practise. Issue 3 (14th February 2019) - Akarca, D; Durnford, A; Ewbank, F; Hempenstall, J; Sadek, A; Gould, A; Bulters, D
Abstract : Objectives: External ventricular drain (EVD) dislodgement is common and can lead to significant morbidity and mortality. UK trial data suggests dislodgement as high as 12%. This study aimed to establish the range of methods used nationally and determine the most secure method in a porcine model. Design: Survey and experimental study. Subjects: 23 neurosurgical units surveyed. Porcine cadaver experimental model. Methods: Survey distribution was made through the British Neurosurgical Trainee Research Collaborative. 15 securement methods were tested on the porcine model and peak pull-out force before EVD failure was measured. Failure was defined as catheter displacement 1 cm from the insertion site, catheter fracture or suture fracture. Results: Nationally, five EVD securement methods were in common use. There were considerable differences in peak pull-out force between methods. The most secure methods were a construct consisting of anchoring suture, further multiple sutures around a coil of catheter followed by either a soft (25.85N, 95% CI 24.95 N-26.75N) or hard plastic flange (29.05N, 95% CI 25.69 N-32.41N). Individually, anchoring sutures, soft flanges, VentriFix and staples were least secure, whilst multiple sutures and hard flanges were most secure. Conclusions: An anchoring suture followed by a coil of catheter and a flange is the most secure method for securing EVDs, withstanding up to 8.2 times the force of a single anchoring suture. It is easily employed and may decrease the likelihood of EVD dislodgement and associated complications.